2022
DOI: 10.1002/advs.202200106
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Space‐Time‐Coding Digital Metasurface

Abstract: Recent progress in space-time-coding digital metasurface (STCM) manifests itself a powerful tool to engineer the properties of electromagnetic (EM) waves in both space and time domains, and greatly expands its capabilities from the physical manipulation to information processing. However, the current studies on STCM are focused under the synchrony frame, namely, all meta-atoms follow the same variation frequency. Here, an asynchronous STCM is proposed, where the meta-atoms are modulated by different time-codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…However, all the above studies on space-time programmable metamaterials are carried out in a synchronous framework, that is, all the meta-atoms on the aperture share the same modulation frequency. Hence, an asynchronous space-time programmable metamaterial is proposed, where the metaatoms are manipulated by different time coding periods (Wang et al, (2022b)). It is shown that when the metamaterial is operated under asynchronous conditions (all meta-atoms no longer share the same manipulating frequency), the reflected waves will generate dynamic scattered wavefronts in space due to the scattering echoes of each element.…”
Section: Asynchronous Space-time Programmable Metamaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all the above studies on space-time programmable metamaterials are carried out in a synchronous framework, that is, all the meta-atoms on the aperture share the same modulation frequency. Hence, an asynchronous space-time programmable metamaterial is proposed, where the metaatoms are manipulated by different time coding periods (Wang et al, (2022b)). It is shown that when the metamaterial is operated under asynchronous conditions (all meta-atoms no longer share the same manipulating frequency), the reflected waves will generate dynamic scattered wavefronts in space due to the scattering echoes of each element.…”
Section: Asynchronous Space-time Programmable Metamaterialsmentioning
confidence: 99%
“…It is shown that when the metamaterial is operated under asynchronous conditions (all meta-atoms no longer share the same manipulating frequency), the reflected waves will generate dynamic scattered wavefronts in space due to the scattering echoes of each element. Therefore, the phase gradient between the Wang et al, (2022b). meta-atoms is no longer constant with time, resulting in the time-varying characteristics of the scattered EM waves.…”
Section: Asynchronous Space-time Programmable Metamaterialsmentioning
confidence: 99%
“…In fact, such an approach can be feasible and generalized through a space-time-coding digital metasurface with field-programmable-gate-array (FPGA) technology, particularly in the microwave regime 29 37 In such a case, different metasurface responses can be digitized by controlling the bias voltages with the adoption of FPGA, which offers the metasurface powerful programmability for space-time modulation.…”
Section: Introductionmentioning
confidence: 99%
“…The phases and/or amplitudes of the STC digital metasurfaces are encoded both in space and time so as to simultaneously manipulate the propagation direction (space domain) and harmonic distribution (frequency domain) of EM waves. STC digital metasurfaces have been applied in many exciting areas such as reciprocal reflection [37], harmonic beam steering [35,38], scattering suppression [35,39], joint multi-harmonic control [40], polarization syntheses [41], analog signal processing [42], direction finding [43], nonuniform periodic modulation [44], multiplexed wireless communication [45].…”
Section: Introductionmentioning
confidence: 99%